Contextual Methodology in the Social Sciences: Historiography, Middle-Range-Theory, & Models - Betz, Frederick (Advances in Social Sciences Research Journal, 2016)
For a cross-disciplinary social science, methodology needs to effectively integrate research across the different social science disciplines. This is an important issue for the social sciences disciplines to be practically useful for policy issues which apply to a whole society. We propose (1) an integrative methodology which grounds middle-range social science theories, upon an empirical basis of modeling historical events. As in all of science, explanation is the key to the validation of theory – all theory should be based upon empirical evidence. Theory not constructed upon nor validated by experiment/observation is methodologically speculative and not proven true. Histories of events in a society can provide empirical grounds for social science theory, as kinds of ‘natural’ societal experiments.